2007
DOI: 10.1179/174328107x155330
|View full text |Cite
|
Sign up to set email alerts
|

Slab quality improvement by controlling mould fluid flow

Abstract: Cleanliness of steel is a primary requirement for flat products. It is obtained with minimum of defects by controlling the liquid flow characteristics in the mould and fluctuations over the meniscus surface. Liquid flow in the mould region is due to the momentum of the pouring stream which in turn is related to the clogging of submerged entry nozzle and argon flow in the mould. This makes control of liquid steel flow dynamics in the mould important. The mould level fluctuation index, flow fraction or clogging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…For Case III the jet develops without alterations, losing kinetic energy uniformly by viscous dissipation as it approaches the narrow wall. As has been reported [32], the quality of steel-among other variables-depends on the solidification process and the flow feeding by the SEN. In other work [29] it was reported that the fluid dynamic structure depends exclusively on the design of the SEN, but due to the results found in this study it is possible to add that it also depends on the depth of immersion in the mold.…”
Section: Velocity Fieldmentioning
confidence: 74%
See 2 more Smart Citations
“…For Case III the jet develops without alterations, losing kinetic energy uniformly by viscous dissipation as it approaches the narrow wall. As has been reported [32], the quality of steel-among other variables-depends on the solidification process and the flow feeding by the SEN. In other work [29] it was reported that the fluid dynamic structure depends exclusively on the design of the SEN, but due to the results found in this study it is possible to add that it also depends on the depth of immersion in the mold.…”
Section: Velocity Fieldmentioning
confidence: 74%
“…However, as indicated [39] a static free surface can cause problems of overcooling and inhibition of steel-slag contact, causing some quality problems in the product. The level oscillations in a single plane in the mold have been reported [32]; however, being a three-dimensional and transient phenomenon, the oscillation profile changes significantly along such thickness. Figure 8 shows the level oscillations in PII, PIII and PIV at the simulation times of 640, 530 and 720 s for the three cases analyzed.…”
Section: Velocity Fieldmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding is also in accordance with literature where Zhang et al (2007) also found increase in metal slag inclusion during ladle change. Also, Kumar et al 2007 reported deviation of the mould level fluctuation index from optimum value during ladle change for operational plant. So, these reported cases of mould level fluctuation or slag entrapment defects during ladle change operation gives us confidence in our finding.…”
Section: Exploratory Data Analysismentioning
confidence: 98%
“…Kumar et al (2007) developed an mould level fluctuation index in an operational plant and the plant data suggests deviation of the index from the optimum values during ladle change and width change due to asymmetry in the flow. Gursoy (2014) investigates effect of different flow controllers on the mould fluid flow including during ladle change.…”
Section: Literature Reviewmentioning
confidence: 99%